Phlebotominae sand flies in Paraguay. Abundance distribution in the southeastern region - Salomón, Oscar Daniel (2003)
Fil: Salomón, Oscar Daniel. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.